A Research on Adaptive Neural Network Control Strategy of Vehicle Yaw Stability - Li Yue-Lin; Huang Ping-Wen; Xie Tao (2013 Fourth International Conference on Intelligent Systems Design and Engineering Applications, 2013)
An adaptive neural network control lerwitn both feed-forward and feedback is designed to improve the yaw stability of vehicle by compound control of direct yaw moment and active front steering. The feedback controller takes the deviation of actual yaw rate from objective yaw rate as its input by PD control strategy,whereas the feed-forward controller uses the output of feedback controller as the error for study through RBF neural network,so as to achieve adaptive control.The simulations show that using above mentioned compound control can effectively track the objective yaw rate and reduce the sideslip angle of mass center,enhancing the stability of vehicle in high-speed sharp turns.